دور الصيرفة الاسلامية في تعزيز الشمول المالي دراسة حول عينة من البنوك البدر -البركة-السلام 2012-2019 - حنان عدواني; احلام باسي (جامعة الوادي University Of Eloued, 2024)
"تهدف الدراسة الى التعرف على دور الصيرفة الإسلامية في إرساء وتعزيز الشمول المالي، ومن خلال دراستنا استعراضنا اهم المفاهيم الخاصة بالصيرفة الإسلامية، وصيغ التمويل والخدمات والمنتجات التي تُقدمها، والهيئات التي تؤطرها والتعرف على الشمول المالي، وأهميتهِ، وأهدافه التنموية. وقد اعتمدنا على المنهج الوصفي التحليلي، وسلطنا الدراسة على احد اهم بنوك الجزائر وهي البدر ولسلام والبركة وخَلُصت الدراسة الاَّ أن الصيرفة الاسلامية رغم التجربة الفَتِية والمتأخرة لها في الجزائر، الا انها تُساهم في إرساء الشمول المالي؛ اذ تُقدم منتجات وخدمات تُعطي خيارات متنوعة لكل الفئات، عبر القنوات الرسمية لتحقيق الرفاة والاندماج الاجتماعي والاقتصادي. " The study aims to identify the role of Islamic banking in establishing and promoting financial inclusion, and through our study, we reviewed the most important concepts of Islamic banking, financing formulas, services and products that it provides, and the bodies that frame it and identify financial inclusion, its importance, and its development goals. We have relied on the descriptive analytical approach, and we highlighted the study on one of the most important banks in Algeria, namely Al-Badr, Salam and Al-Baraka, and the study concluded that Islamic banking, despite the young and Late experience in Algeria, but it contributes to the establishment of financial inclusion, as it provides products and services that give a variety of options for all categories, through official channels to achieve welfare and socio-economic integration.
Keywords: الصيرفة الإسلامية- الشمول المالي- صيغ الصيرفة الإسلامية- البنوك الجزائرية; Islamic banking-financial inclusion-Islamic banking formulas-Algerian banks